1998
DOI: 10.1074/jbc.273.36.23225
|View full text |Cite
|
Sign up to set email alerts
|

The Rabbit 15-Lipoxygenase Preferentially Oxygenates LDL Cholesterol Esters, and This Reaction Does Not Require Vitamin E

Abstract: The oxidation of low density lipoprotein (LDL) by mammalian 15-lipoxygenases (15-LOX) was implicated in early atherogenesis. We investigated the molecular mechanism of 15-LOX/LDL interaction and found that during short term incubations, LDL cholesterol esters are oxygenated preferentially by the enzyme. Even when the LDL particle was loaded with free linoleic acid, cholesteryl linoleate constituted the major LOX substrate. In contrast, only small amounts of free oxygenated fatty acid isomers were detected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 43 publications
5
62
0
3
Order By: Relevance
“…It is shown that cholesterol ester is selectively transferred from the LDL particle to the plasma membrane via LRP in Y1 murine adrenocortical cells (14) and in our 12/15-lipoxygenase-expressing cells 2 and that linoleic acid esterified to cholesterol in the LDL particle is regio-and stereospecifically oxygenated by the 12/15-lipoxygenase-expressing cells (12). Thus, the above observations strongly support our contention that the 12/15-lipoxygenase associated with the membranes oxygenates cholesterol ester transferred to the membrane, because self-catalyzed inactivation of the 12/15-lipoxygenase, which should be observed in the enzyme reaction with cholesterol ester in the membrane, is known to occur (23). This would explain the much lower enzyme activity in membranes.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/supporting
confidence: 78%
See 2 more Smart Citations
“…It is shown that cholesterol ester is selectively transferred from the LDL particle to the plasma membrane via LRP in Y1 murine adrenocortical cells (14) and in our 12/15-lipoxygenase-expressing cells 2 and that linoleic acid esterified to cholesterol in the LDL particle is regio-and stereospecifically oxygenated by the 12/15-lipoxygenase-expressing cells (12). Thus, the above observations strongly support our contention that the 12/15-lipoxygenase associated with the membranes oxygenates cholesterol ester transferred to the membrane, because self-catalyzed inactivation of the 12/15-lipoxygenase, which should be observed in the enzyme reaction with cholesterol ester in the membrane, is known to occur (23). This would explain the much lower enzyme activity in membranes.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/supporting
confidence: 78%
“…However, the reduction of the enzyme activity may be due to other mechanisms unrelated to suicide inactivation such as poor substrate availability or conformational changes of the enzyme. It is reported that 12/15-lipoxygenase preferentially oxygenates cholesterol ester in the LDL particle, whereas phospholipids or even free fatty acids are not oxygenated, although they are present on the surface of the LDL particle (23). These results suggest that the specific oxygenation of cholesterol ester transferred to the plasma membrane by 12/15-lipoxygenase could take place.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/mentioning
confidence: 60%
See 1 more Smart Citation
“…1 12/15-Lipoxygenase (12/15-LO) is a nonheme ironcontaining dioxygenase that forms 12-hydroperoxyeicosatetraenoic acid (12-HPETE) and 15-HPETE and oxidizes esterified fatty acids in lipoproteins (cholesteryl esters) and phospholipids. 2,3 On the basis of its product from arachidonic acid, it is classified as 15-lipoxygenase (15-LO) in humans and rabbits 4,5 and as "leukocyte-type" 12-lipoxygenase (12-LO) in pig, rat, and mouse. 6 12/ 15-LO can also produce 13-hydroperoxy-octadecadienoic acid (13-HPODE) from linoleic acid.…”
mentioning
confidence: 99%
“…15-and 12͞15-LOXs play a central role in vascular disease, because (i) 15-LOX mRNA, protein, and lipid products are found in atheroma, (ii) inhibition of 15-LOX prevents atherosclerosis in rabbits, and (iii) functional inactivation of the 12͞15-LOX gene slows down aortic lipid deposition in apo E-deficient mice, and inhibits streptozotocin-induced diabetes (19)(20)(21)(22)(23)(24)(25). Furthermore, in vivo, 12͞15-LOX expression is required for neointimal thickening in ballooninjured rat aortae (26,27).…”
Section: ͞15-lipoxygenase (Lox) Activity Is Elevated In Vascular DImentioning
confidence: 99%